2007 IEEE International Symposium on Signal Processing and Information Technology 2007
DOI: 10.1109/isspit.2007.4458016
|View full text |Cite
|
Sign up to set email alerts
|

A Leaf Recognition Algorithm for Plant Classification Using Probabilistic Neural Network

Abstract: Abstract-In this paper, we employ Probabilistic Neural Network (PNN) with image and data processing techniques to implement a general purpose automated leaf recognition for plant classification. 12 leaf features are extracted and orthogonalized into 5 principal variables which consist the input vector of the PNN. The PNN is trained by 1800 leaves to classify 32 kinds of plants with an accuracy greater than 90%. Compared with other approaches, our algorithm is an accurate artificial intelligence approach which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
436
0
28

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 698 publications
(465 citation statements)
references
References 19 publications
1
436
0
28
Order By: Relevance
“…The Flavia dataset was collected by Wu et al [21], it contains 1907 RGB scans images of leaf. It is composed of 32 species; where, each species has 40 to 60 sample leaves.…”
Section: Flavia Datasetmentioning
confidence: 99%
“…The Flavia dataset was collected by Wu et al [21], it contains 1907 RGB scans images of leaf. It is composed of 32 species; where, each species has 40 to 60 sample leaves.…”
Section: Flavia Datasetmentioning
confidence: 99%
“…The source of images of leaves used in this study is images of leaves found in the Flavia dataset which is publicly available (Wu et al, 2007). The Flavia dataset is a constrained set of leaf images taken against a white background and without any stem present.…”
Section: Data Setmentioning
confidence: 99%
“…Works using such biosonar sensors for natural landmark classification were also proposed in [9] and [10]. Another method for plant classification was proposed by Wu et al [11]. They are using a computer vision leaf recognition algorithm to determine features describing the leaf's shape and size, and a probabilistic neural network (PNN) to learn the relation.…”
Section: Related Workmentioning
confidence: 99%